Stowed away - Ross, Barbara, 1953- (Ross, Barbara, 1953- Maine clambake mystery, 2018)
When Julia's old prep school rival Wyatt Jayne invites her to dinner on board her billionaire fiancé's decked-out yacht, Julia arrives to find a sumptuous table set for two--and the yachtsman dead in his chair. Suspicion quickly falls on Wyatt, and Julia's quest to dredge up the truth leads her into the murky private world of a mega-rich recluse who may not have been all that he seemed--